Política e fissuras sobre crianças e jovens: psiquiatria, neurociência e educação - Oliveira, Salete (Ecopolítica, 2011)
Hoje, os investimentos neurocientíficos e psiquiátricos sobre crianças e jovens intensificam-se. Apresentam sinalizações, não negligenciáveis, para uma educação preventivo- terapêutica, acoplada à rotinização de diagnósticos e tratamentos educativos em espaços variados. A psiquiatria se renova, também, no interior dela própria, pelo que vem sendo chamado de “psiquiatria do desenvolvimento”, mais recente variação da designada “psiquiatria da infância e adolescência”. Interessa, neste momento, traçar o funcionamento de novas formas de monitoramentos sutis que objetivam aplacar rebeldias e os investimentos neuropsiquiátricos voltados à formação de crianças e jovens resilientes. Palavras-chave: resiliência, controle, psiquiatria, política, prevenção. Policies and fissures on children and youth: psychiatry, neuroscience and education Abstract: In present days, the neuroscientific and psychiatric investments on children and adolescents have intensified. They bring about undeniable signals for an education based on prevention and therapy, combined with the routinization of diagnosis and educative treatments in various spaces. The psychiatry renews itself, also in its interior, by what has been called “psychiatry of development” – the most recent variation of the so-called “psychiatry of infancy and adolescence”. What matters, at the moment, is to outline the functioning of new and subtle ways of monitoring that aims at hampering resistances and on neuropsychiatric investments intended to educate resilient children and adolescents. Keywords: resilience, control, psychiatry, politics, prevention.